ANALISIS GAYA BELAJAR DIFERENSIASI TERINTEGRASI BUDAYA(CRT) PADA MATERI EKONOMI MENGGUNAKAN PEMBELAJARAN BERBASIS MASALAH - ISTIKA, WIDHA; HARTONO, WINEKAS; SISWANTO, JOKO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This study examines the learning styles of 4th grade elementary school students in economics material, with special attention to visual, auditory and kinesthetic aspects. The research aims to understand the relationship between basic economic concepts and students' cultural backgrounds, as well as finding related local economic activities. It is hoped that the research results can help develop diverse learning methods, especially with culturally responsive teaching approaches. This qualitative research used literature study at SDN Palebon 02 Semarang, involving 27 grade IV students. Data was collected through observation, unstructured interviews and documentation. The analysis used the Miles and Hubberman method, including reduction, presentation and drawing conclusions. Findings: The learning styles of class IV students at SDN Palebon 02 Semarang varied (auditory 37%, visual 33%, kinesthetic 30%). Differentiated learning integrates Culturally Responsive Teaching and Problem Based Learning, including differentiation of content, processes and products. The use of media and activities is adapted to learning styles, accompanied by integration of local culture and continuous evaluation to improve learning. .Class 4B of SDN Palebon 02 shows various learning styles: visual 33%, auditory 37%, and kinesthetic 30%. This approach increases meaningful learning experiences and motivation. It is recommended that teachers implement differentiated learning with Culturally Responsive Teaching using Problem Based Learning by linking the material to the local economic culture of Semarang, can encourage active participation, and pay attention to student diversity through interactive media and cultural artifacts. ABSTRAKStudi ini meneliti gaya belajar siswa kelas 4 SD pada materi ekonomi, dengan perhatian khusus pada aspek visual, auditori, dan kinestetik. Penelitian bertujuan memahami hubungan antara konsep ekonomi dasar dan latar belakang budaya siswa, serta menemukan aktivitas ekonomi setempat yang berkaitan. Diharapkan hasil penelitian dapat membantu mengembangkan metode pembelajaran yang beragam, terutama dengan pendekatan pengajaran yang responsif terhadap budaya.Penelitian kualitatif ini menggunakan studi pustaka di SDN Palebon 02 Semarang, melibatkan 27 siswa kelas IV. Data dikumpulkan melalui observasi, wawancara tidak terstruktur, dan dokumentasi. Analisis menggunakan metode Miles dan Hubberman, mencakup reduksi, penyajian, dan penarikan kesimpulan.Hasil temuan: Gaya belajar siswa kelas IV SDN Palebon 02 Semarang bervariasi (auditori 37%, visual 33%, kinestetik 30%). Pembelajaran berdiferensiasi mengintegrasikan Culturally Responsive Teaching dan Problem Based Learning, mencakup diferensiasi konten, proses, dan produk. Penggunaan media dan aktivitas disesuaikan dengan gaya belajar, disertai integrasi budaya lokal dan evaluasi berkelanjutan untuk perbaikan pembelajaran. .Kelas 4B SDN Palebon 02 menunjukkan gaya belajar beragam: visual 33%, auditori 37%, dan kinestetik 30%. Pendekatan ini meningkatkan pengalaman belajar bermakna dan motivasi. Disarankan guru menerapkan pembelajaran berdiferensiasi dengan Culturally Responsive Teaching menggunakan Problem Based Learning dengan mengaitkan materi dengan budaya ekonomi lokal Semarang, dapat mendorong partisipasi aktif, dan memperhatikan keragaman siswa melalui media interaktif dan artefak budaya.